PENGARUH MODEL PEMBELAJARAN NUMBERED HEADS TOGETHER TERHADAP HASIL BELAJAR SISWA KELAS IV SD (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was determine the effect of Numbered Heads Together (NHT) learning model on the learning outcomes and responses of fourth-grade elementary school students. The model used was an experiment with a nonequivalent control group pretest-posttest design. The research subjects consisted of 50 students. Data collection techniques included student response questionnaires and learning achievement assesments. Data analysis results showed that the average pretest score for the experimental class was 69.7 and the posttest score was 84.6, while the control class had a pretest score of 65.55 and a posttest score was 83.6, the t-test results of the hypothesys test showed a significance value of 0.023. Considering that the significance level of 0.023 < 0.05, which means H0 is fulfilled, it can be concluded that the Numbered Heads Together approach has an impact on the learning outcomes of fourth-grade elementary school students. Learning outcomes are significantlly influenced by the Numbered Heads Together model resulting in positive responses with 83% of fourth-grade students stating that they feel comfortable using the Numbered Heads Together model.